Legal Status of Legal Entity State Universities regarding the Implementation of Public-Private Partnership - Laksono, Wahyu Agung; Amalia, Prita; Nurzaman, R. Adi (Jurnal Manajemen Pelayanan Publik, 2025)
The presidential regulation provides a policy that provides a regulatory basis for government cooperation with business entities, including cooperation carried out by state universities as legal entities. However, the position of state universities as legal entities has characteristics as determined by the Law on Higher Education, so that there are legal problems related to the legal position of state universities as legal entities in implementing government cooperation with business entities and the absence of government support for state universities as legal entities for implementing government cooperation with business entities. The research method uses a normative legal research method that focuses on library data using the legal interpretation analysis method with analytical descriptive presentation. The results of the study indicate that state universities as legal entities are required to consider management independence, funding sources, development planning, funding concepts, and delegation of authority in terms of obtaining legal standing for implementing government cooperation with business entities. State universities as legal entities also need to get support from the Ministry of Education, Culture, Research and Technology as a government institution that oversees state universities as legal entities through the preparation of regulations on implementing government cooperation with business entities within the Ministry of Education, Culture, Research and Technology.